Kesiapan Guru Pendidikan Agama Islam Dalam Memanfaatkan Infografis Di Era Digital - Lathif, Sahro Wardil; Nadhiroh, Yulsifa Anissatun; Rusydiyah, Evi Fatimatur (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This research aims to analyze the readiness of Islamic Religious Education (PAI) teachers in utilizing infographics as a learning medium in the digital era. With a case study-based qualitative approach, this research explores teachers' understanding, technical skills, and pedagogical awareness of the use of infographics. The research results show varying levels of readiness, influenced by minimal understanding of concepts, limited technical skills, and lack of confidence in the effectiveness of infographics. Apart from that, limited facilities and technological support also become obstacles in implementation. The proposed solution includes intensive training, improving technological facilities, as well as providing concrete examples of the use of infographics in learning. This research emphasizes the importance of infographics as a relevant medium in 21st century learning, especially for clarifying abstract concepts in PAI subjects.